Розробка CRM-системи автосервісу - Самойлов, А. І. (ХНУРЕ, 2024)
Nowadays information technologies consist a huge part of our daily life. A lot of business owners try to move their business on-line. It is a great idea because it helps to get more clients and to promote business development. There is a lot of online stores that allows us to buy different kinds of services and stuff. Unfortunately, they are consisting a lot of disadvantages, but it the reason why we should try to develop site, that works without any bugs. I decided to create an information system for auto-service owners. It is much easier to clients to look at stage that their car is, and it is the reason why this system is relevant.
Keywords: інтерфейс користувача; база даних клієнтів; управління замовленнями; облік послуг; система резервування